2013
DOI: 10.1128/jb.01986-12
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of a Class I Holin, P2 Y

Abstract: Y is the putative holin gene of the paradigm coliphage P2 and encodes a 93-amino-acid protein. Y is predicted to be an integral membrane protein that adopts an N-out C-in membrane topology with 3 transmembrane domains (TMDs) and a highly charged C-terminal cytoplasmic tail. The same features are observed in the canonical class I lambda holin, the S105 protein of phage lambda, which controls lysis by forming holes in the plasma membrane at a programmed time. S105 has been the subject of intensive genetic, cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Gene Y encodes a holin, which allows the P2 lysozyme, the product of gene K, to access the peptidoglycan. 43,44 The lysA gene product functions as an antiholin, needed to delay the action of gpY until the optimal lysis time. 43,44 Amber mutants in lysB exhibit delayed lysis in non-permissive cells.…”
Section: The Lysis Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene Y encodes a holin, which allows the P2 lysozyme, the product of gene K, to access the peptidoglycan. 43,44 The lysA gene product functions as an antiholin, needed to delay the action of gpY until the optimal lysis time. 43,44 Amber mutants in lysB exhibit delayed lysis in non-permissive cells.…”
Section: The Lysis Genesmentioning
confidence: 99%
“…43,44 The lysA gene product functions as an antiholin, needed to delay the action of gpY until the optimal lysis time. 43,44 Amber mutants in lysB exhibit delayed lysis in non-permissive cells. 43 The lysC gene, which overlaps the lysB gene, was originally identified by a mutation that overcomes the P2 growth defect conferred by a temperature-sensitive mutation in the b' subunit of RNA polymerase.…”
Section: The Lysis Genesmentioning
confidence: 99%
“…Because RI is a specific inhibitor of T, it is formally a member of a diverse class of proteins designated antiholins (23)(24)(25)(26). Moreover, since RI inhibits T only under certain physiological conditions, it is the only antiholin known that transduces environmental information to effect real-time control of holin function and thus of the length and fecundity of the phage infection cycle (21).…”
mentioning
confidence: 99%
“…Similar nonspecificity and permissiveness for the large endolysin chimeras had been noted for other holins, the Y holin from coliphage P2 and the T holin from coliphage T4 (9,10). Recently, cryo-electron microscopy (cryo-EM) studies revealed that both of these holins formed similar micrometer-scale interruptions in the inner membrane (IM) (11).…”
mentioning
confidence: 86%
“…Recently, another holin, P2 Y, although lacking detectable similarity to S105, has been shown to adapt the same topology and follow the same general pathway, including triggering to form micrometer-scale holes (9). It also has two TMDs that have faces with widely disparate hydrophobic characters, but in this case, they are TMD2 and TMD3 rather than TMD1 and TMD3, as in S105.…”
Section: Discussionmentioning
confidence: 99%